2018
DOI: 10.1002/adhm.201701046
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Controlling Differentiation of Adult Stem Cells for Peripheral Nerve Regeneration

Abstract: Adult stems cells, possessing the ability to grow, migrate, proliferate, and transdifferentiate into various specific phenotypes, constitute a great asset for peripheral nerve regeneration. Adult stem cells' ability to undergo transdifferentiation is sensitive to various cell-to-cell interactions and external stimuli involving interactions with physical, mechanical, and chemical cues within their microenvironment. Various studies have employed different techniques for transdifferentiating adult stem cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 235 publications
(341 reference statements)
1
46
0
Order By: Relevance
“…Although several studies indicated that engineering 3D microenvironments enabled better control of stem cell fates and effective regeneration of functional tissues (27)(28)(29)(30), there were no studies concerning the establishment of 3D-bioprinted microenvironments that can preferentially induce MSCs differentiating into glandular cells with multiple tissue phenotypes and overall functional tissue. To find an optimal microenvironment for promoting MSC differentiation into specialized progeny, biochemical properties are considered as the first parameter to ensure SG specification.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies indicated that engineering 3D microenvironments enabled better control of stem cell fates and effective regeneration of functional tissues (27)(28)(29)(30), there were no studies concerning the establishment of 3D-bioprinted microenvironments that can preferentially induce MSCs differentiating into glandular cells with multiple tissue phenotypes and overall functional tissue. To find an optimal microenvironment for promoting MSC differentiation into specialized progeny, biochemical properties are considered as the first parameter to ensure SG specification.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Specifically, electrodes comprising graphene and graphene derivatives (graphene nanoparticles, reduced graphene oxides, oxidized graphene, functionalized graphene) have demonstrated high electrical conductivity and/or catalytic capability. For example, in the past decade graphene has been used for electrode materials in electrochemical devices such as supercapacitors, 4 batteries, 5 fuel cells, 6 cell electrode stimuli 7,8 and sensors. 9,10 Graphene is typically produced by chemical vapor deposition (CVD) which can yield nearly pristine (defect-free) single or few layer 2D sheets.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are three main challenges that need to be addressed for the clinical transition of this strategy. These challenges include (1) precise control on the final fate of the implanted cell population during the in vivo regeneration period, (2) non-scalable differentiation protocols, and (3) design of multifunctional conduit with desired properties that mimics the complex extracellular matrix microenvironment [16][17][18][19]. Thus, addressing these challenges makes tMSCbased strategies a viable solution for PN injury repair.…”
Section: Introductionmentioning
confidence: 99%